Senior Citizens Protesting at Exhibit Hall Mayor Dan Whitehurst Funding Policies - Watkins, Howard::::::::: (1981)
Kathy Reilley holding WHITEHURST protest sign; Senior Citizens carrying signs "I'm too old to Walk 8 Blocks to Bus Stop, Restore All Buses"